Lactic acid production via cassava-flour-hydrolysate fermentation (2012)
ABSTRACT : Background: Lactic acid (LA) is a carboxylic acid widely used as preservative, acidulant, and/or f la-vouring in food industry; it is also used as a raw material for the production of lactate ester, propylene glycol, 2,3-pentanedione, propanoic acid, acrylic acid and acetaldehyde. In recent years, the demand for LA production has dramatically increased due to its application as a monomer for poly-lactic acid synthesis, a biodegradable polymer used as a plastic in many industrial applications. LA can be produ-ced either by fermentation or chemical synthesis; the former route has received considerable interest, due to environmental concerns and the limited nature of petrochemical feedstocks; thus, 90% of LA produced worldwide is obtained by fermentation, this process comprises the bioconversion of a sugar solution (carbohydrates) into LA in the presence of a microorganism. Objectives: This work is aimed at studying the effect of pH control and culture media composition on the LA production using renewable sources from the agroindustry sector. Methods: A Lactobacillus brevis strain is used to perform lab scale experiments under aerobic and anaerobic conditions, using three different culture media compositions: a high nutritional content medium (MRS), as a reference, a low nutritional content medium with glucose as the only carbon source (GM), and a potential low nutritional content medium with cassava f lour as carbon source (HY1). Results: The higher LA production is accomplished under anaerobic conditions, 17.6 ± 0.1, 12.6 ± 0.2 y 13.6 ± 0.2 g LA/L, for MRS, GM and HY1 medium, respectively. The effect of pH on LA biosynthesis in a 5L bioreactor is also studied using the HY1 medium. For a fermentation time of 120 h, the highest LA concentration obtained was 24.3 ± 0.7g LA/L, productivity 0.20 g/L/h, YP/S 0.32g LA/g syrup, at pH 6.5. Conclusions: These results are comparable with those using expensive carbon sources such as glucose, and show cassava f lour as a promising low-cost substrate source for lab and eventually large scale LA biosynthesis.